Improving competitive appreciative value with competitive Learning model and cooperative learning for mathematics in grade Sixth of elementary school no.01 koto pulai kecamatan lengayang - Asna Yarni (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Implementation of Education at elementary level aims to provide stock to students to live in society and can continue Education to a higher level. One of the areas of teaching in elementary education is mathematics. Mathematics is the study of patterns and relationships, a way or pattern of thinking, an art, a language and a tool according to Reys et al. (Ruseffendi 1990: 2). Mathematics as a tool that is, where human beings to think in finding the truth. The truth discovery in resolving the issues in general and in solving the problems that use mathematics in particular, for example, the number can be used a tool for understanding algebra and calculus while other subjects that require mathematics include Physics, economics, astronomy. The purpose of this study, in accordance with the problems that have been raised are: To know the improvement of learning concept of KPK and FPB through Cooperative learning model CCL in Class VI Koto Pulai No.01 Elementary School District of Lengayang. To know student achievement through Cooperative learning model CCL in KPK and FPB learning at Class VI Koto Pulai No.01 Elementary School District of Lengayang. The form of this research that is carried out is a classroom action research (Clasroom action research). Classroom action research is a reflective form of research by taking action- Certain actions in order to improve and / Classroom teaching practice in a more professional manner. (Suyanto, 1997: 4). Therefore PTK is a form of research that has characteristics related to the problems that departfrom the problem of learning practices faced by teachers everyday, from the problem then the teacher needs to solve the problem professionally Based on the results obtained by students with an average of 8.2 with the greatest results 10 and the smallest 4, for that based on reflection and interviews on student results obtained a picture that there are still students who are not careful in completing KPK and FPB and the mistake to determine the step From determining the KPK and FPB and also there are mistakes in calculating the sum, division and multiplication, from this can be obtained the picture as according to Mercer and Mercer (in Armanto, 1990: 58), as for learning with this model Has begun to appear successful in understanding the concept of KPK and FPB and Cooperative learning